Disruption management in single wagonload transport - Maurice Krauth; Daniel Haalboom; Henning Preis; Nikola Bešinović (Transportation Research Interdisciplinary Perspectives)
In highly utilised rail networks, disruptions can quickly have extensive impact on overall network performance, significantly affecting the reliability and efficiency of transport chains. Dealing immediately with disruptions is important to maintain satisfactory operation level. We propose managing disruptions in single wagonload (SWL) transport by optimising the rerouting and reassigning of railway wagons. Our model, DIMENSION, minimises total delay of railway wagons as well as deviation of train services from the nominal schedule. The model performance is demonstrated on multiple different sized networks derived from real-world German SWL network. We conduct computational experiments considering different demands for each network. Results show that the impact of a disruption increases with increasing demand, that the location of a disruption has major influence, and that increasing network size is not necessarily leading to a higher impact of a disruption. Varied network demand results confirm these findings. The proposed model enables to evaluate the impact of disruptions on SWL networks and supports dispatchers to optimise the routing of railway wagons as well as the scheduling of train services. By optimising network performance during disruptions, DIMENSION helps improving the reliability and quality of transport chains.